2015
DOI: 10.3366/ijhac.2015.0141
|View full text |Cite
|
Sign up to set email alerts
|

Homer's Iliad – A Social Network Analytic Approach

Abstract: In this paper we provide some insights in Homer's Iliad from the perspective of social network analysis. We use the original text and other public available data to create a social network (i.e. a graph) that comprises of all actors in the Iliad together with their interactions. We present some visualizations of these data and discuss concepts like connectivity, connected components and groupings. Furthermore, we calculate some well-established metrics, coming from social network analysis in this social networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…This can be due to several reasons. The first is that some groups of people are mentioned in an indistinguishable way in the raw material, for instance: townfolks in Twain's Huckleberry Finn [126], Olympian gods and Greek soldiers in Homer's Iliad [259], bypassers in certain plays [137,172] and novels [75]. Second, it can also be that some characters always appear simultaneously in the plot: considering them collectively can be viewed as some form of simplification.…”
Section: Graph Extractionmentioning
confidence: 99%
“…This can be due to several reasons. The first is that some groups of people are mentioned in an indistinguishable way in the raw material, for instance: townfolks in Twain's Huckleberry Finn [126], Olympian gods and Greek soldiers in Homer's Iliad [259], bypassers in certain plays [137,172] and novels [75]. Second, it can also be that some characters always appear simultaneously in the plot: considering them collectively can be viewed as some form of simplification.…”
Section: Graph Extractionmentioning
confidence: 99%
“…Both [31] and [32] found that epic works like The Iliad are scale-free networks with respect to the actor's interactions. The same results come from [33] regarding modern literature.…”
Section: Kydros a Anastasiadismentioning
confidence: 99%
“…Previous studies on character networks [21,23,7,8,9] have used what we call the aggregate network, that is all connections made along a plot are considered together, irrespective of whether they are, at some point of the narrative, no longer extant. For the sake of completeness we show what the aggregate networks of Alice and Roland look like in Figs.…”
Section: The Chapter-by-chapter Casementioning
confidence: 99%
“…Without pretending to be exhaustive, these authors calculated a series of measures for the complete, friendly and hostile graphs and showed that some of the networks in these texts bear a striking resemblance to social networks from the real world, an indication that the stories they depict could have some elements drawn from real events [8]. A more detailed analysis of the Iliad beyond that of [7] can be found in [9]. In all the aforementioned studies one does not differentiate the time in the narrative where the link is made, so there is no dynamics involved.…”
Section: Introductionmentioning
confidence: 99%